The Influence of Online Customer Reviews and Celebrity Endorsers on Impulsive Buying of Skintific Products on TikTok Shop in Mataram City - Fajryani, Dinda; HS, Rusminah (Universitas KH. Abdul Chalim Mojokerto, 2026)
This study was conducted to determine the extent to which Online Customer Reviews and Celebrity Endorsers influence impulsive buying behavior on Skintific products through the TikTok Shop platform in Mataram City. Online Customer Reviews are defined as user reviews or experiences that serve as a source of information about product quality and shape the confidence of potential consumers. Meanwhile, Celebrity Endorsers are public figures who promote products by utilizing their image, reputation, and personal influence. TikTok Shop, as a social commerce media, provides various features such as comment columns, review displays, and live selling that can strengthen the role of these two factors in generating purchasing decisions. The research findings show that Online Customer Reviews have a positive and significant influence on Impulsive Buying with a t-value of 6.216, higher than the t-table of 0.660, and a significance level of 0.000 <0.05. In addition, Celebrity Endorsers are also proven to have a positive and significant influence with a t-value of 3.416 greater than the t-table of 0.660 and a significance level of 0.002 <0.05. Therefore, both variables are considered capable of encouraging consumers to make spontaneous purchases of Skintific products through TikTok Shop.